Nuclear war : a scenario - Jacobsen, Annie (Dutton, 2024)
"Every generation, a journalist has looked deep into the heart of the nuclear military establishment: the technologies, the safeguards, the plans, and the risks. These projects are vital to how we understand the world we really live in: where one nuclear missile begets one in return; where the choreography of the world's end requires massive decisions made on seconds-notice, with information that is only as good as the intelligence we have. Annie Jacobsen's Nuclear War: A Scenario explores this ticking clock scenario, based on dozens of new interviews with military and civilian experts who have built the weapons; created the response plans; and been responsible for those decisions should they need to have been made. Nuclear War: A Scenario is unlike any other book in its depth and urgency"--